Strategi Pembelajaran Bernyanyi Lagu Daerah di SMP Negeri 7 Padang - Muthia Rahmawati; Hengki Armez Hidayat (EDUMUSIKA, 2023)
This research aims to understand how best to help students learn about art and culture. This study uses a type of qualitative research with a descriptive analysis approach. The researcher is the main research instrument, equipped with supporting tools such as cellphones and stationery. Observations, interviews, literature, and documentation were all used as data collection methods. Data were analyzed by identifying data, classifying data, clarifying data, analyzing data, describing it, and concluding. The results showed that at Padang 7 Public Middle School the learning process for singing folk songs had not been carried out properly and the learning objectives were not optimally achieved, because the strategies used by the teacher during the learning process were less effective. Teachers tend to only use the lecture method, thus making student learning outcomes less than optimal, this can be seen from student activities during the learning process.